THE EFFECT OF LOW BIRTH WEIGHT (LBW) ON NEONATAL DEATH IN GORONTALO CITY - Ahmad I. Mohune; Sunarto Kadir; Lintje Boekoesoe (UNG, 2023)
Indonesia is a developing country with high maternal and infant mortality rates. One of the causes of infant mortality in Indonesia is the incidence of Low Birth Weight (LBW) of 38.85%. The number of neonatal deaths in Gorontalo City between 2018 - 2021 is 83 cases. The novelty of this research is the effect of LBW on neonatal death. This study aims to see the impact of LBW on neonatal mortality in Gorontalo City after controlling for maternal risk factors in the form of a history of complications and the frequency of ANC. The research design used was analytic with a case-control approach. The sample in this study consisted of 30 cases and 60 controls. The results of the survey show that from the effects of bivariate analysis, the history of complications variable has an Odds Ratio Crude value of 55 and an Odds Ratio Adjusted of 13 and the Mantel-Haenszel test value: p-value α (0.000 0.05). In contrast, Antenatal Care has an Odds Ratio Crude value of 28 and Odds Ratio Adjusted by 17 and the value of the Mantel-Haenszel test: p-value α (0.000 0.05). The Odds Ratio value for LBW is 20 with a p-value α (0.000 0.05). This study concludes that LBW has a 20 times risk of neonatal death (95% CI = 6.506 – 61.485)